2021
DOI: 10.1186/s12879-021-05980-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving treatment outcomes for leprosy in Pernambuco, Brazil: a qualitative study exploring the experiences and perceptions of retreatment patients and their carers

Abstract: Background Brazil has a high leprosy burden and poor treatment outcomes (TOs), manifesting in high relapse rates. Pernambuco, an impoverished Brazilian state suffering notable geographical health inequalities, has ‘hyperendemic’ leprosy. Although current literature identifies barriers and facilitators influencing leprosy treatment compliance, inadequate investigation exists on other factors influencing TOs, including carers’ roles and psycho-dermatological impact. This qualitative study explore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 83 publications
(118 reference statements)
2
29
0
1
Order By: Relevance
“…The most frequently absent detail in the included studies was the information on the influence of the researcher on the research (question 7, S5 Appendix); only five studies reported this item. [34,45,58,62,73] Seventeen studies [12,19,43,44,47,59,63,65,[69][70][71][75][76][77]79,80,83] had no obvious statement locating the researcher culturally or theoretically.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The most frequently absent detail in the included studies was the information on the influence of the researcher on the research (question 7, S5 Appendix); only five studies reported this item. [34,45,58,62,73] Seventeen studies [12,19,43,44,47,59,63,65,[69][70][71][75][76][77]79,80,83] had no obvious statement locating the researcher culturally or theoretically.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…This synthesised finding consisted of three categories and 43 findings from 27 studies. [12,16,18,[43][44][45][48][49][50]52,54,[58][59][60][62][63][64][65][66][67]72,76,78,[81][82][83]87] This synthesis documented the effects of leprosy on the skin, eyes, wounds on their limbs, nerve injury, and pain. Due to poor access to healthcare and delays in treatment, the individuals suffering from leprosy developed deformities that impacted their day-to-day activities.…”
Section: India and Indonesiamentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with identified missing demographics were sought in further sampling processes. 20 The interview was arranged within 2 days after the in-person training. The qualitative data collection and analysis occurred in a concurrent and iterative fashion.…”
Section: Methodsmentioning
confidence: 99%